Особливості римування сонетів Яра Славутича (на прикладі циклів “Херсонські сонети” та “Перше кохання”) - Накашидзе, Ірина Сергіївна (Купрієнко С.В., Одесса, 2020)
UKR: У роботі розглядається специфіка римування сонетів у циклах “Херсонські сонети” та “Перше кохання” збірки Яра Славутича “Співає колос” .Визначено, що Сонети Яра Славутича належать до класичних, італійських. Для них характерне інтонаційне розмаїття. Яр Славутич використовував велику кількість коротких римованих рядів, що дало змогу показати свою оригінальність. Коли автор не знаходив української рими, він використовував власні неологізми з метою досягнення милозвучності та ритмомелодики вірша. У сонетах Яра Славутича рими переважно точні, асонансні та відкриті. У його римах всі звуки співзвучні. Для створення ритмомелодики поет у всіх сонетах циклів чергує жіночі, або парокситонні, та чоловічі, або окситонні, рими. Рими у сонетах Яра Славутича циклів “Херсонські сонети” та “Перше кохання” виконують функції підсилення емоційного звучання вірша, створення ритму, завершенності кожного віршового рядка, мелодійності та багатство вірша.

ENG: The purpose of this article is to study the specifics of rhyming sonnets in the series "Kherson Sonnets" and "First Love" of poetic collection "Spike is singing" by Yar Slavutych. Yar Slavutych's sonnets belong to the classical, Italian ones. They are characterized by intonational diversity. Most of them have a classical system of rhyming the final words of the poem abba-abba-ccd-ede. Although the poet used a purely authorial rhyming system abba-abba-cdc-ddc or abba-baba-cdc-dee. Yar Slavutych used a large number of short rhyming series, which made it possible to show his originality. When the author could not find Ukrainian rhyme, he used his own neologisms in order to achieve the melodiousness and rhythmic melody of the poem. In Yar Slavutych's sonnets the rhymes are mostly precise, assonant and open. In his rhymes all sounds are consonant. To create rhythmic melodies, the poet alternates feminine, or paroxytonic, and masculine, or oxytonic, rhymes in all the sonnets of the cycles. As a result of the research it can be concluded that the rhymes in Yar Slavutych's sonnets of the cycles "Kherson Sonnets" and "First Love" perform the functions of strengthening the emotional sound of the poem, creating rhythm, completeness of each verse, melody and richness of the poem.
Rhyming Features of Yar Slavutych's Sonnets (On the Example of Cycles “Kherson Sonnets” and “First Love”)
І. Накашидзе: ORCID 0000-0002-7816-2339
Keywords: жанр сонета; система римування; асонансні та консонансні рими; окситонні та парокситонні рими; римовий ряд; ритмомелодика; sonnet genre; rhyming system; assonant and consonant rhymes; oxytonic and paroxytonic rhymes; rhyme series; rhythmic melody; КУ